Atrial Fibrillation in Patients Hospitalized With COVID-19: Incidence, Predictors, Outcomes, and Comparison to Influenza - Musikantow, Daniel R. (JACC Clin Electrophysiol, 2021)
OBJECTIVES: The goal of this study is to determine the incidence, predictors, and outcomes of atrial fibrillation (AF) or atrial flutter (AFL) in patients hospitalized with coronavirus disease-2019 (COVID-19). BACKGROUND: COVID-19 results in increased inflammatory markers previously associated with atrial arrhythmias. However, little is known about their incidence or specificity in COVID-19 or their association with outcomes. METHODS: This is a retrospective analysis of 3,970 patients admitted with polymerase chain reaction–positive COVID-19 between February 4 and April 22, 2020, with manual review performed of 1,110. The comparator arm included 1,420 patients with influenza hospitalized between January 1, 2017, and January 1, 2020. RESULTS: Among 3,970 inpatients with COVID-19, the incidence of AF/AFL was 10% (n = 375) and in patients without a history of atrial arrhythmias it was 4% (n = 146). Patients with new-onset AF/AFL were older with increased inflammatory markers including interleukin 6 (93 vs. 68 pg/ml; p < 0.01), and more myocardial injury (troponin-I: 0.2 vs. 0.06 ng/ml; p < 0.01). AF and AFL were associated with increased mortality (46% vs. 26%; p < 0.01). Manual review captured a somewhat higher incidence of AF/AFL (13%, n = 140). Compared to inpatients with COVID-19, patients with influenza (n = 1,420) had similar rates of AF/AFL (12%, n = 163) but lower mortality. The presence of AF/AFL correlated with similarly increased mortality in both COVID-19 (relative risk: 1.77) and influenza (relative risk: 1.78). CONCLUSIONS: AF/AFL occurs in a subset of patients hospitalized with either COVID-19 or influenza and is associated with inflammation and disease severity in both infections. The incidence and associated increase in mortality in both cohorts suggests that AF/AFL is not specific to COVID-19, but is rather a generalized response to the systemic inflammation of severe viral illnesses.